Partial reform and the Chinese bureaucracy in the post Mao era - Zhou Xueguang (1995)
"Using 1987 survey data of 1988 bureaucrats in eight large cities, I examine the effect of the recent economic reform on the Chinese bureaucracy - the distribution of bureaucrats in different types of organizations, jobs, hierarchical positions, and bureaucratic compensation. The results show mixed characteristics of the Chinese bureaucracy in the partial reform where market and planning, competence and political loyalty coexist. There is evidence of the continuing dominance of the party state on bureaucratic personnel management. On the other hand, significant changes took place in the selection criteria, and to a lesser extent, in the institutional structure, as evidenced in the promotion patterns and bureaucratic compensation. These results point to the evolving organizational basis of state socialism in the transition process"
Keywords: Civil service reform - China; Bureaucracy - China; Civil service - China